Social Freedom and Critical Theory: The Tension Axel Honneth’s Political Philosophy and his Critical Programme - László G. Szücs (RUDN Journal of Philosophy, 2025)
Axel Honneth’s work Das Recht der Freiheit - Grundriss einer demokratischen Sittlichkeit (2011) is an original attempt at a synthesis: you can read it as a classical work on political philosophy and as a program of a renewal of a critical social theory. Since he wrote the book, he has held lectures about the philosophy of social freedom in connection with some basic ideas of the book. The investigation of these lectures makes it possible for us to focus more on the book’s philosophical profile and analyze it in the context of the classical philosophical tradition. In my study, I give an outline of this political-philosophical profile when I reconstruct the thread of thought with which Honneth works out the theory of “social freedom.” According to my presumption, we can see the emergence of a political philosopher who reconsiders the arguments of classical political philosophers in a very innovative way. At the same time, some weaknesses of Honneth’s synthesis can be pointed out while reconstructing his theory. By approaching classical philosophical tradition, Honneth contradicts the program from which he hopes to gain the renewal of a critical theory based on “dialogue” and social analysis. In this study, I will compare Axel Honneth’s critical social theory as it is outlined in this work with his critical assumptions as they unfold in his earlier works. I also critique, from the perspective of the unfolding thought process, Honneth’s analysis of social pathologies in relation to the concept of “law” and the concept of “negative freedom”.